REM sleep without atonia is associated with increased rigidity in patients with mild to moderate Parkinson’s disease - Linn-Evans, Maria E. (Clin Neurophysiol, 2020)
OBJECTIVE: Increased muscle activity during rapid eye movement (REM) sleep (i.e. REM sleep without atonia) is common in people with Parkinson’s disease (PD). This study tested the hypotheses that people with PD and REM sleep without atonia (RSWA) would present with more severe and symmetric rigidity compared to individuals with PD without RSWA and age-matched controls. METHODS: Sixty-one individuals participated in this study (41 PD, 20 controls). An overnight sleep study was used to classify participants with PD as having either elevated (PD-RSWA+) or normal muscle activity (PD-RSWA-) during REM sleep. Quantitative measures of rigidity were obtained using a robotic manipulandum that passively pronated and supinated the forearm. RESULTS: Quantitative measures of forearm rigidity were significantly higher in the PD-RSWA+ group compared to the control group. Rigidity was significantly more asymmetric between limbs in the PD-RSWA− group compared with controls, while there was no significant difference in symmetry between the control and PD-RSWA+ groups. CONCLUSION: In people with mild to moderate PD, RSWA is associated with an increased and more symmetric presentation of upper limb rigidity. SIGNIFICANCE: Dysfunction of brainstem systems that control muscle tone during REM sleep may contribute to increased rigidity during wakefulness in people with PD.